2017
DOI: 10.1128/msphere.00291-16
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Chemical Adaptation to Endogenous Hydrogen Peroxide Production in Streptococcus pneumoniae D39

Abstract: Adaptation to endogenous oxidative stress is an integral aspect of Streptococcus pneumoniae colonization and virulence. In this work, we identify key transcriptomic and proteomic features of the pneumococcal endogenous oxidative stress response. The thiol peroxidase TpxD plays a critical role in adaptation to endogenous H2O2 and serves to limit protein sulfenylation of glycolytic, capsule, and nucleotide biosynthesis enzymes in S. pneumoniae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 93 publications
6
75
0
1
Order By: Relevance
“…Although a few studies have reported that endogenous H 2 O 2 protects streptococci from challenge with a higher H 2 O 2 concentration (8,22), the mechanism remains unclear. In the present study, through a combination of physiological, biochemical, genetic, and redox proteomic studies, we elucidated the mechanism underlying the low-H 2 O 2 -concentration-induced adaptation of catalase-negative streptococci to a higher H 2 O 2 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have reported that endogenous H 2 O 2 protects streptococci from challenge with a higher H 2 O 2 concentration (8,22), the mechanism remains unclear. In the present study, through a combination of physiological, biochemical, genetic, and redox proteomic studies, we elucidated the mechanism underlying the low-H 2 O 2 -concentration-induced adaptation of catalase-negative streptococci to a higher H 2 O 2 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication (Lisher et al, 2017) demonstrated that tpxD level is increased by 6.8 following growth with limited aeration compared with growth under anaerobic condition. These authors show that TpxD plays a major role in preventing endogenous protein sulfenylation by H 2 O 2 , reinforcing our conclusion that TpxD is required for the bacterial response to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae is the most common bacterial pathogen, that is responsible for invasive pneumococcal diseases, and can produce considerable amounts of H2O2 [130][131][132]. Hamada and his It has been shown after robust activation signals, various kinds of immune cells release granular proteins and chromatin into the cellular microenvironment (extracellular space), forming DNA-based extracellular traps.…”
Section: Mitochondrial Dna and Anti-bacterial Immunitymentioning
confidence: 99%